2020
DOI: 10.1021/acssuschemeng.9b06429
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Preserving Extraction and Characterization of Biomass Extrinsic and Intrinsic Inorganic Compounds

Abstract: The inorganic content of biomass impairs size reduction tool life and the conversion process. Conventional ash extraction relies on furnace combustion that inevitably alters the inorganic compounds due to oxidation and decomposition. This study developed composition-preserving methods for extracting and analyzing extrinsic and intrinsic inorganic compounds. Comprehensive characterization was carried out on selected biomass feedstocks, including corn stover, pine residue, and pine anatomical fractions, to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The wood chip sizes before and after rotary shear processing are 30 × 30 × 10 and 15 × 10 × 6 mm 3 , respectively. The wood chips were first dried, and the EIPs were then extracted from 1 kg of each feedstock sample using a composition-preserving extraction method developed earlier . The weight percentages were measured to determine the content of EIPs for 1 kg of the woodchips before and after comminution.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wood chip sizes before and after rotary shear processing are 30 × 30 × 10 and 15 × 10 × 6 mm 3 , respectively. The wood chips were first dried, and the EIPs were then extracted from 1 kg of each feedstock sample using a composition-preserving extraction method developed earlier . The weight percentages were measured to determine the content of EIPs for 1 kg of the woodchips before and after comminution.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Biomass inorganic content (often called “ash”) has been found to be largely responsible for the processing tool wear. , There is intrinsic inorganic content inside the plant cells and tissues as a result of normal physiological processes and extrinsic inorganic particles (EIPs), typically soil or dust contamination either adhered to the biomass surface or collected during harvest. The abrasiveness of the biomass feedstock depends on the concentration, chemical composition, and particle size and shape of the inorganic compounds. EIPs were reported with high hardness of 6.5–7.5 Mohs. , Detailed characterizations of the inorganic compounds of corn stover and pine residue have been conducted recently . The wear of the hammer mill was investigated, and erosion was determined to be the dominant wear mode as a result of high-speed impact with the biomass inorganic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Task 1 currently focuses on issues related to wear and durability of components used in unit operations to pretreat feedstocks arriving from the field/forest to the entrance of biochemical or thermal reactors where the feedstocks are converted into useful products. Studies [6,7] have shown that mechanical wear can be significant, with wear clearly visible to the naked eye. The wear can add significant delays in processing feedstocks due to high downtimes to replace worn components, but also to clear jams that occur in milling units.…”
Section: Figure 1 Illustration Of Physical Form Of Corn Stover Feedstmentioning
confidence: 99%
“…These operations include bale processing (deconstruction/shredding of corn stover bound up into square/rectangular or round bales weighing approximately ½ ton) and size-reduction operations to yield loose, free flowing biomass that can be readily treated by downstream pretreatment and conversion/digestion processes. Additional processing steps are often used to remove rock, gravel, sand and nonferrous metallic contaminants and to classify/separate the biomass by size and anatomical fractions prior to size reduction operations [6]. Figure 1 illustrates the flow diagram of major preprocessing operations used in the comminution of biomass feedstock.…”
Section: Introduction/backgroundmentioning
confidence: 99%